s = 2πr(r+h)
s/2πr = r+h
(s/2πr)-r = h
Make h the subject of the formula s= 2πr(r+h)
13 answers
Be careful with brackets
s= 2πr(r+h)
s/(2πr) = r + h
h = s/(2πr) - r
X's solution would be dividing only by 2 not by 2πr
s= 2πr(r+h)
s/(2πr) = r + h
h = s/(2πr) - r
X's solution would be dividing only by 2 not by 2πr
Math
Just I want to familiar in mathematics
Please
97,000
I explain in detail
Solve this m² = ( √st/2 - rhq ) make h the subject of formula
Make b the subject of the formula Br=abr-cbt
h=67/g8h/3
Make x the subject of the formular 2xr(h+r)
I = prt/100 make p the subject
bruh khan academy question